2010
DOI: 10.1111/j.1749-6632.2010.05828.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of antibacterial discovery revisited

Abstract: The discovery of novel antibiotic classes has not kept pace with the growing threat of bacterial resistance. Antibiotic candidates that act at new targets or via distinct mechanisms have the greatest potential to overcome resistance; however, novel approaches are also associated with higher attrition and longer timelines. This uncertainty has contributed to the withdrawal from antibiotic programs by many pharmaceutical companies. Genomic approaches have not yielded satisfactory results, in part due to nascent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
129
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(132 citation statements)
references
References 97 publications
(194 reference statements)
0
129
0
3
Order By: Relevance
“…Genes that are specific to bacteria were deleted to determine which genes were essential for bacterial viability 201 and to identify antibacterial targets. However, such efforts have not yielded the success that was anticipated [201][202][203] and no new drugs emerged [204][205][206] . A G " K mpaigns revealed that 67 HTS campaigns against targets that were selected from a panel of 160 genes that had been predicted to be essential for microbial viability failed to generate candidates for clinical development 203 .…”
Section: Opportunities For Natural Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes that are specific to bacteria were deleted to determine which genes were essential for bacterial viability 201 and to identify antibacterial targets. However, such efforts have not yielded the success that was anticipated [201][202][203] and no new drugs emerged [204][205][206] . A G " K mpaigns revealed that 67 HTS campaigns against targets that were selected from a panel of 160 genes that had been predicted to be essential for microbial viability failed to generate candidates for clinical development 203 .…”
Section: Opportunities For Natural Productsmentioning
confidence: 99%
“…Perhaps the promise that was offered by genomic approaches took attention from the fact that successful development of antibacterial drugs is always particularly challenging 202,204,206 .…”
Section: Opportunities For Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Halen de kullanmakta olduğumuz bu ajanlar, bakterilerin bellibaşlı fizyolojik süreçleri üzerinde etkili olurlar. Bunlar, hücre duvarı biyosentezi (β-laktamlar, glikopeptidler), hücre zarı (lipopeptidler, polimiksinler), tip II topoizomerazlar (florokinolonlar), ribozomlar (makrolidler, aminoglikozidler, tetrasiklinler, glisilsiklinler, oksazolidinonlar, streptograminler), transkripsiyon (rifampisin) ve folat biyosentezi (sülfonamidler ve trimetoprim) olarak sıralanabilir (2).…”
unclassified
“…Given current trends in infectious disease, it's unfortunate that the scientific, regulatory, and economic challenges of antibiotic research have led to a decline in the approval of new agents [4,5,[8][9][10][11][12][13]. Today, there are few new antibiotics in late stage development offering activity against the most dangerous hospital acquired gram-negative pathogens [14][15][16].…”
Section: Introductionmentioning
confidence: 99%